2013
DOI: 10.1039/c3ib20259c
|View full text |Cite
|
Sign up to set email alerts
|

Non-dimensional analysis of retinal microaneurysms: critical threshold for treatment

Abstract: Fluid dynamics play a fundamental role in the development of diabetic retinopathy, one of the leading causes of blindness in the Western world, affecting over 4 million people in the US alone. The disease is defined by microaneurysms, local expansions of capillaries that disturb the hemodynamic forces experienced by the endothelium leading to dysfunction, leakage and edema. Here we present a method to identify microaneurysms with a high risk of leakage based on a critical ratio of microaneurysm to vessel diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Several studies have evaluated the pathogenesis and natural history of MAs using ex vivo (e.g., transmission electron microscopy and scanning electron microscopy) and in vivo (scanning laser ophthalmoscopy and optical coherence tomography) imaging approaches to characterize pericyte loss, basement membrane thickening, and endothelial proliferation and disruption (Wise, 1957 ; Cogan et al, 1961 ; de Oliveira, 1966 ; Ashton, 1974 ; Moore et al, 1999 ). One study (Ezra et al, 2013 ) proposed using MA-to-vessel radius ratio as a potential marker for assessing risk of leakage, and suggested that shear stress at the MA wall may lead to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the pathogenesis and natural history of MAs using ex vivo (e.g., transmission electron microscopy and scanning electron microscopy) and in vivo (scanning laser ophthalmoscopy and optical coherence tomography) imaging approaches to characterize pericyte loss, basement membrane thickening, and endothelial proliferation and disruption (Wise, 1957 ; Cogan et al, 1961 ; de Oliveira, 1966 ; Ashton, 1974 ; Moore et al, 1999 ). One study (Ezra et al, 2013 ) proposed using MA-to-vessel radius ratio as a potential marker for assessing risk of leakage, and suggested that shear stress at the MA wall may lead to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysms’ data was integrated with our previously published criteria of aneurysm risk of rapture [ 7 ]. A schematic of the database with its different associations is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A more substantial ‘data to knowledge’ utility of this database can be developed. For example, our predictive model of aneurysms’ risk of rapture uses a non-dimensional analysis of fluid dynamics to set a critical geometrical threshold of treatment [ 7 ]. Piccinelli and colleagues could derive geometrical measures of patients’ aneurysms’ geometries, which can be used with the prediction model to determine risk of rapture [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Ezra et al [ 130 ] suggested that the microaneurysm radius/associated vessel diameter ratio might be a useful metric for predicting leakage risk.…”
Section: Multimodal Imaging Of Microvascular Abnormalities In Retimentioning
confidence: 99%